Bacterial Strain Improvement via Random Physical Mutation to Improve Phosphate Solubilization Efficiency for Sustainable Crop Growth - Damor, S.; Goswami, P. (Journal of Scientific Research, 2024)
Phosphorus deficiency in soil due to cation-mediated fixation reduces agricultural output from otherwise fertile lands. Phosphate solubilizing bacteria can solubilize this immobilized phosphate. The goal of this study was to use random UV mutagenesis to improve the phosphate solubilizing efficiency of the bacterial strains isolated from agriculture soils of Jaipur, Rajasthan. The phosphate solubilizing capacity was determined using the colorimetric chlorostannous reduced molybdo phosphoric acid blue method. When UV treated for 40, 50, and 60 min. Strain B5 depicted 58.54 %, 133.27 %, and 159.09 % enhanced phosphate solubilization, respectively, in the phylogenetic tree constructed using 16S rRNA gene sequencing, the isolate B5 clustered with Pseudomonas putida strains. Thus wild strains such as Pseudomonas sp. and Bacillus sp. can be mutagenically exploited to avail incapacitated phosphorus in soil. This can be an ecologically desired elucidation; however, more research is needed to investigate the underlying mechanisms involved and their repercussions.